Pengaruh Likuiditas dan Solvabilitas terhadap Kinerja Keuangan (Studi pada Perusahaan Tambang Sektor Batu Bara yang Terdaftar di Daftar Efek Syariah Tahun 2018–2022) - Silfi Afrianti; Usdeldi; Marissa Putriana (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The ratio of liquidity and solvency is the most dominant ratio seen by investors in assessing the financial condition of a company, because this second analysis is considered a simple form of analysis but is good for recommendations. This study aims to determine the effect of liquidity and solvency on financial performance in mining companies in the coal sector that are registered on the sharia securities list for 2018 – 2022. The number of samples in this study were 8 companies and used a purposive sampling technique. Statistical methods using multiple linear analysis, t test, F test, and analysis of the coefficient of determination. The results showed that solvency has a significant effect on financial performance, while liquidity has no significant effect on financial performance. By using the F test it is known that liquidity and solvency have a simultaneous influence on financial performance. Calculation of the coefficient of determination shows that all independent variables are 0.560 or 56%, meaning that financial performance can be explained by liquidity and solvency of 56%, while 44% can be explained by other factors such as company size, asset management, and others.